Changes in connexin 43 in inflammatory skin disorders: Eczema, psoriasis, and Steven‐Johnson syndrome/toxic epidermal necrolysis. Issue 1 (19th February 2021) - Tan, Mandy L. L.; Kwong, Hui L.; Ang, Chia C.; Tey, Hong L.; Lee, Joyce S. S.; Becker, David L.
Abstract: Background: Connexin 43 (Cx43) plays a central role in the inflammatory response and wound healing. Targeting Cx43 expression reduces inflammation in a variety of injuries. The expression pattern of Cx43 has not been described for many inflammatory skin diseases. Objectives: To describe the expression patterns of Cx43 in eczema, psoriasis, Steven‐Johnson syndrome/toxic epidermal necrolysis. Methods: Archival skin biopsies from patients with eczema, psoriasis, and Steven‐Johnson syndrome/toxic epidermal necrosis were identified and examined, with sister sections stained for Cx43 and imaged by confocal microscopy. All samples were compared to age and site‐matched normal skin controls. Results: Epidermal Cx43 is reduced in acute eczema, absent in regions of spongiosis, and is highly elevated in subacute and chronic eczema. In plaque psoriasis, Cx43 is overexpressed in areas with psoriasiform hyperplasia with a fish‐scale‐like appearance but is lost in regions surrounding neutrophil microabscesses. Cx43 staining is strong in the neutrophils within these microabscesses. In SJS/TEN, Cx43 expression is elevated in areas bordering normal tissue but is rapidly lost in areas of keratinocyte necrosis. Conclusions: Dynamic changes in Cx43 levels are seen in inflammatory skin diseases and may represent future potential therapeutic targets. Abstract : Connexin 43 (Cx43) plays a central role in the inflammatory response and wound healing. Targeting Cx43 expression reduces inflammation in a variety of injuries. Here we examine the changes in Cx43 protein levels in the epidermis in eczema, psoriasis, Steven‐Johnson Syndrome/Toxic Epidermal necrolysis.